Pengembangan dan Pelatihan Literasi Digital dan Strategi Branding Sosial Media UMKM Sektor Laundry di Kota Depok - Ahmad Dzaky Pratama; Sagita Pradyaningrum; Muhammad Alif Al Adrunisapta; Ramdani Eka Pradana; Afifah Latifah Turahma; Suci Ayu Sudari; Yuni Pambreni; Nora Listiana; Udriyah Udriyah; Nur Fitri Dewi (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
The laundry service MSME sector in Depok City faces significant challenges in the form of intense competition and reliance on conventional marketing methods, resulting in low visibility in the digital era. The objective of this community service activity is to improve the digital literacy and branding skills of laundry MSME operators in the Beji area to Grand Depok City. The implementation method uses a participatory-educational approach that includes three stages: pre-implementation (survey and needs identification), implementation (strategic seminars and hands-on workshops), and evaluation. The results of the activity show that through education on digital marketing strategies, customer complaint management using the LEARN method, and practical video editing training using the CapCut application, participants are able to transform their business identity to be more professional. The success of this program is marked by increased competence of participants in optimizing Instagram Business accounts and producing creative, aesthetic content. Strengthening digital literacy and visual skills has proven to be key for laundry MSMEs in building brand awareness and maintaining customer loyalty sustainably amidst the dynamics of the modern market.